The Rosary and its accounts: associative networks and citizenship of members of the Brotherhood of Nossa Senhora do Rosário do Pelourinho (Salvador, 1880-1930) - Santos, Mariana de Mesquita (Revista Crítica Histórica, 2022)
The practice of affiliation to black brotherhoods and other mutual support associations was recurrent in the 19th century among Africans and Afro-Brazilians. Often it happened as a way of accumulating not only benefits, but also prestige in society. In the city of Salvador it was no different and some researchers have highlighted these associative networks. In this article, we investigate the profile of some brothers and sisters of the brotherhood of Rosário at Portas do Carmo and we analyze the different meanings of the proximities established between members of the brotherhood with the mutual societies emerging in the Bahian capital from the second half of the 19th century, as well as with other Afro-religious devotional spaces. Indeed, we understand that the trajectories of subjects associated with the Afro-Bahian brotherhood also included involvement with post-abolition political and social activism.